2005
DOI: 10.1007/s11104-004-4781-4
|View full text |Cite
|
Sign up to set email alerts
|

Spatial root distribution of apricot trees in different soil tillage practices

Abstract: Root and soil water distribution was studied in a mature drip-irrigated apricot (Prunus armeniaca L. cv. Bu´lida) orchard with different soil tillage practices, in a loamy textured soil with a 7% slope, located in Murcia (SE Spain). Three treatments were applied between tree rows: control (no-tillage), whereby, following the common practice in the area, weeds were cut back to ground level by a blade attached to a tractor; perforated treatment, where the soil surface was mechanically perforated with an adaptedp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(33 citation statements)
references
References 24 publications
1
29
0
3
Order By: Relevance
“…This led to an increase in infiltration due of the increase in hydraulic conductivity. Thus, soil surface tillage treatments might facilitate infiltration during rainfall events, reducing runoff (Ruiz-Sánchez et al, 2005). Under the present experimental conditions, the flux of water entry into the soil was characterised by the relative dominance of gravity over the capillary forces, independent of the water pressure head imposed.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…This led to an increase in infiltration due of the increase in hydraulic conductivity. Thus, soil surface tillage treatments might facilitate infiltration during rainfall events, reducing runoff (Ruiz-Sánchez et al, 2005). Under the present experimental conditions, the flux of water entry into the soil was characterised by the relative dominance of gravity over the capillary forces, independent of the water pressure head imposed.…”
Section: Resultsmentioning
confidence: 82%
“…It is important to note that the low hydraulic conductivity values measured in the control treatment (Table 2), together with the slope of the orchard (» 7%), could be a cause of notable runoff under non-tilled conditions (Ruiz-Sánchez et al, 2005). Angulo-Jaramillo et al (1997) reported similar hydraulic conductivity in sandy-loam and sandy soils Effect of tillage and pressure head on soil hydraulic properties 183 Table 2).…”
Section: Resultsmentioning
confidence: 98%
“…Roots were collected after the soil was passed through a 0.5-mm sieve with the aid of a water jet. Debris, weeds and dead roots were sorted by hand from the 'live' roots during washing, based on visual observation that the 'live' roots appeared light in colors (Oikeh et al 1999;Qu et al 2003;Ruiz et al 2005). Each plant component was washed with distilled water, dried in an oven at 70°C for 72 h, and weighed.…”
Section: Sampling and Measurement Methodsmentioning
confidence: 99%
“…Root studies under field conditions are labour intensive and the destructive methods involved make repeated measurements at the same site virtually impossible (Böhm, 1979;Ruiz-Sánchez et al, 2005). Recent studies describe the use of ground-penetrating radar (GPR) as a non-invasive means for field root investigations, although the technique is limited to coarse roots (Guo et al, 2013).…”
Section: Introductionmentioning
confidence: 99%